MINERALOGICAL AND GEOCHEMICAL CHARACTERIZATION OF HYDROCARBON SEEP SEDIMENTS FROM THE GULF OF MEXICO - Canet C.; Prol-Ledesma R.M.; Mortera-Gutiérrez C.; Linares C.; Escobar-Briones E.; Cruz R.L.S.; Cienfuegos E.; Morales-Puente P. (My University, 2006)
A common characteristic of the Gulf of Mexico (GOM) seafloor, hydrocarbon seepage produces asphalt volcanism, brine pools, gas hydrates and authigenic carbonates. We studied authigenic carbonates from two areas: Green Canyon (Louisiana slope, 1000 mbsl) and the Chapopote diapir (abyssal plain, southwestern GOM, 2900 mbsl). Carbonates consist of oily, matrix-supported limestones with variable porosity and a fine-grained matrix of calcite. They occur in Green Canyon as both concretions formed below the seafloor and as slabs of seabed pavements. In each case, the carbonates are mudstones with a mud matrix consisting of high-Mg calcite, disseminated pyrite and detrital quartz. The carbonate slabs have vug microporosity and contain barite that occurs as vug lining. The precipitation of barite results from a reaction between barium-rich and sulfate-free seep fluids and downwards-diffusing seawater. The carbonates in Chapopote occur in relation to tar flows and form crusts of wackestones with bivalve shells. The matrix is composed by low-Mg calcite with disseminated pyrite and detrital quartz. The carbonate mud shows depletion in 13C, with δ13C between -36.9‰ and -23.0‰. Carbonates precipitate as a consequence of anaerobic methane oxidation coupled with seawater sulfate reduction. δ18O values (3.4-4.4‰) suggest precipitation at temperatures between 5 and 9 °C. © 2006 Elsevier Ltd. All rights reserved.
Keywords: BARITE; CARBONATES; COLD SEEPS; STABLE ISOTOPES